Pengaruh Leverage, Kualitas Audit, dan Whistleblowing terhadap Integritas Laporan Keuangan yang Dimoderasi oleh Manajemen Laba - Sherlin Clarita; Riris Rotua Sitorus (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
The purpose of this study is to analyze the effect of leverage, audit quality, and reporting of violations on the integrity of financial statements moderated by earnings management. This study uses data taken from financial statements originating from the Indonesia Stock Exchange (IDX) with purposive sampling that meets the exploration steps. The study period was taken for 5 years from 2017 to 2021 with 90 data from 18 banking sub-sector entities. The study method uses STATA with secondary data types. The results of the study explain that partially leverage and audit quality affect the integrity of financial statements positively, while whistleblowing partially does not affect the integrity of financial statements. The results of the moderating variable state that earnings management is able to moderate leverage and audit quality on report integrity and earnings management in this study is not able to moderate the Whistleblowing relationship on financial statement integrity.